Cardiovascular disease risk in people with severe mental disorders: an update and call for action. Issue 4 (July 2022) - Rødevand, Linn; Tesli, Martin; Andreassen, Ole A.
Abstract : Purpose of review: Cardiovascular disease (CVD) is a major cause of premature death in people with severe mental disorders (SMDs). This review provides an update on the level of CVD mortality and morbidity, as well as the socioeconomic, psychosocial and genetic factors associated with the comorbidity, and offer directions for improved interventions to reduce CVD in SMDs. Recent findings: The level of CVD mortality and morbidity has sustained high in people with SMDs during the past decades, but the causal mechanism must be further elucidated. Psychosocial and socioeconomic challenges are frequent in SMDs as well as in CVD. Further, recent studies have revealed genetic variants jointly associated with SMDs, CVD risk and social factors. These findings highlight the need for more targeted interventions, prediction tools and psychosocial approaches to comorbid CVD in SMDs. Summary: The level of CVD comorbidity remains high in SMDs, indicating that most people with SMDs have not benefitted from recent medical advances. A complex interplay between genetic and social vulnerability to CVD, which differs across subgroups of patients, seems to be involved. Further research is required to meet the urgent need for earlier, more efficient intervention approaches and preventive strategies for comorbid CVD in SMD.